Intifada hits the headlines : how the Israeli press misreported the outbreak of the second Palestinian uprising - Dor, Danny, 1951- (Indiana series in Middle East studies., 2004)
In this nuanced and detailed study of newspaper reporting during the escalation of the second Intifada in the fall of 2000, Daniel Dor shows how real events are subject to distortion and manipulation by the media. In an analysis of the heart of Israel's media establishment, he finds a wide gap between the reality reported by field reporters and the eventual newspaper accounts framed by editors. Dor argues it is the influence of fear, anger, ignorance, and a desire to please and to sell newspapers that threatens the freedom of the press in a liberal democracy.